2009
DOI: 10.1016/j.resp.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of awareness of change in load on ventilatory response during moderate exercise

Abstract: This study was designed to determine whether awareness of change in load alters ventilatory response during moderate exercise. Subjects performed two incremental exercise protocols on a cycle ergometer. The load was increased from 1.0 to 1.5 kp in steps of 0.1 kp every 3 min. Subjects were provided true information about the load in the control protocol and untrue information that the load would remain constant in the deception protocol. Slope of ventilation against CO 2 output was significantly lower in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Therefore, the findings in the present study not only support the above concept (Amman et al 2013) but also suggest that effort-mediated ventilatory response during fatiguing IE cannot be explained by the conventional framework of central command that drives breathing via neural mechanisms consisting of parallel activation of motor and respiratory centers (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). Recent studies (Decety et al 1991;Thornton et al 2001;Williamson et al 2002Williamson et al , 2006Yunoki et al 2009) using a cognitive approach to dissociate peripheral neural signals from central command have suggested that central command-mediated response does not necessarily require parallel activation of central motor command. Thornton et al (2001) showed by using positron emission tomography (PET) that breathing during imagination of effortful exercise was increased with significant activations of the dorsolateral prefrontal cortex, supplementary motor areas, premotor area, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the findings in the present study not only support the above concept (Amman et al 2013) but also suggest that effort-mediated ventilatory response during fatiguing IE cannot be explained by the conventional framework of central command that drives breathing via neural mechanisms consisting of parallel activation of motor and respiratory centers (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). Recent studies (Decety et al 1991;Thornton et al 2001;Williamson et al 2002Williamson et al , 2006Yunoki et al 2009) using a cognitive approach to dissociate peripheral neural signals from central command have suggested that central command-mediated response does not necessarily require parallel activation of central motor command. Thornton et al (2001) showed by using positron emission tomography (PET) that breathing during imagination of effortful exercise was increased with significant activations of the dorsolateral prefrontal cortex, supplementary motor areas, premotor area, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…They proposed a 'division of attention' during the exercise task as a cause of the attenuated breathing 17,37) . On the other hand, Yunoki et al 38) showed that when subjects performed prolonged moderate incremental exercise, under the condition of being provided false prior information that the workload would remain constant, awareness of change in load and ventilatory response were significantly reduced compared to the control condition in which true prior information was provided (Fig. 1).…”
Section: Quality Of Imagerymentioning
confidence: 98%
“…1). Since magnitudes of RPE (or effort sense) and central motor command (estimated from an integrated EMG of exercising muscle) were similar between the two conditions, they concluded that ventilatory response during moderate exercise depends not so much on effort sense, but more on awareness or attention that is closely connected to information detection 38) . Awareness or attention can be one of the stresses that elicit emotion.…”
Section: Quality Of Imagerymentioning
confidence: 99%
See 2 more Smart Citations